2002
DOI: 10.1002/ajh.10213
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of a patient with end‐stage renal disease with Rituximab: Pharmacokinetic evaluation suggests Rituximab is not eliminated by hemodialysis

Abstract: The purpose of this study was to determine if therapeutic levels of Rituximab could be achieved in a patient with renal failure being dialyzed and if Rituximab is removed by hemodialysis. A 54-year-old man with low-grade lymphoma and renal failure on hemodialysis received 8 weekly treatments of Rituximab at 375 mg/M 2 . Serum Rituximab levels were obtained before and after each treatment, before and after dialysis following each treatment, as well as in the dialysate fluid. The serum levels of Rituximab increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 13 publications
2
37
0
2
Order By: Relevance
“…The blood level of rituximab during hemodialysis was maintained at a higher level than that in a DLBCL patient with normal renal function, with the peak level reached 6 hours after administration, followed by a similar pharmacokinetic pattern as that in the control pa-tient. Jillella et al (8) measured the blood level of rituximab before and after each hemodialysis course and showed that rituximab was not removed by hemodialysis. Our data not only support their finding but also provide very valuable information including detailed pharmacokinetic measurements from the start to 48 hours after administration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The blood level of rituximab during hemodialysis was maintained at a higher level than that in a DLBCL patient with normal renal function, with the peak level reached 6 hours after administration, followed by a similar pharmacokinetic pattern as that in the control pa-tient. Jillella et al (8) measured the blood level of rituximab before and after each hemodialysis course and showed that rituximab was not removed by hemodialysis. Our data not only support their finding but also provide very valuable information including detailed pharmacokinetic measurements from the start to 48 hours after administration.…”
Section: Discussionmentioning
confidence: 99%
“…For these reasons, the patient elected to receive rituximab monotherapy. Jillella et al reported that rituximab represents an unproblematic, safe and successful treatment option for patients with end-stage renal failure on hemodialysis (8). To prove that rituximab was not removed by the dialysis solution and that it was maintained at a therapeutic level in serum, we measured the blood concentration of rituximab by enzyme-linked immunosorbent assay using FALCO Biosystems, Inc. (Kyoto, Japan) (8,9).…”
Section: T H E R I T U X I Ma B L E V E L D U R I N G H E Mo D I a L mentioning
confidence: 99%
“…This agent does not require dose modification in the renal setting; however, it could be responsible for acute and often severe fluid retention (ATRA syndrome), thus requiring careful management and accurate water balance monitoring [78,79]. The novel proteasome inhibitor bortezomib [80], which is used in the management of MM and in selected cases of others HM, and the monoclonal antibody rituximab [81,82], which represents an essential agent for the treatment of most lymphoproliferative disorders, have been safely administered at full doses to patients with RI and to those on HD. Of note, sustained therapeutic serum levels of rituximab comparable with patients with normal renal function were achieved after the infusion of this agent after HD, and no rituximab clearance into the dialysate was found.…”
Section: Reviewmentioning
confidence: 99%
“…Bendamustine is not metabolised in the kidneys and may be given to patients with MGrS without modification due to renal function parameters [33,34]. The use of monoclonal antibodies, including anty-CD20, is safe even for patients with impaired renal function [35,36].…”
Section: Treatment Elimination Of Monoclonal B Clonementioning
confidence: 99%